Analisis Model VisCAP Faktor Pemilihan Jungkook Sebagai Brand Ambassador Calvin Klein 2023 - Salsabila, Reisa; Purbantina, Adiasri (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
The rise in popularity of South Korean culture (Korean Wave) has led many companies to use this as an effective marketing communication strategy. Brand Ambassadors play a crucial role for the fashion industry in executing marketing campaigns. In this context, many global fashion companies have utilized South Korean public figures as brand ambassadors to promote their products. This study focuses on analyzing the factors behind Calvin Klein's decision to choose Jungkook as the brand ambassador for Calvin Klein Jeans and Calvin Klein Underwear in 2023, using the VisCAP approach proposed by Rossiter and Percy. This research employs a descriptive qualitative method with data collection techniques through literature review. The results show that Jungkook meets all four characteristics listed in the VisCAP model, which positively impacts the brand he represents.